102k views
4 votes
6x-x+4=-x-7+5 solve for x

2 Answers

5 votes
Hello there!


\left[\begin{array}{ccc}\boxed{ 6*x-x +4-(-x-7+5)=0 }\end{array}\right] \\ \\ We \ would \ then \ pull \ out \ like \ factors . . . . \\ \\ 6x + 6 = 6 * (x + 1) \\ \\ Solve : 6 = 0 \\ \\ Subtract \ 1 \ from \ both \ sides \ of \ the \ equation : \\ \\ Your \ answer: \ \Longrightarrow \boxed{x = -1 }

I hope this helps you!
User Ketan Ghumatkar
by
6.0k points
3 votes
Lets get started :)

We have to solve for x

6x - x + 4 = - x - 7 + 5

The ideal job to be done is collect the like terms together in order to proceed and find the value of x

6x - x + 4 = - x - 7 + 5

RHS: Right-Hand Side | LHS: Left-Hand Side

We take - x from the RHS to the LHS by adding
When you see minus, you do plus
The same with + 4, we shift it to the RHS from the LHS
When you see plus, you do minus

6x - x ( + x ) + 4 ( - 4 ) = ( + x ) - x - 7 + 5 - 4
- 4 and + 4 cancels out on the LHS and - x and + x cancels out on the RHS
6x - x + x = - 7 + 5 - 4
6x = -6

To find the value of x, we need to divide either side by the coefficient of x, which is 6 in this problem
We do division, when we see multiplication
(6x)/(6) = (-6)/(6)
6 and 6 cancels out on the LHS

Your final answer will be x = -1

User Mbudnik
by
5.9k points